Factors influencing vaccine coverage in Tshwane district, Gauteng, South Africa - Fraser, Heather Lynne (My University, 2019)
Background: It has been well established that immunisation is essential in preventing illnesses and reducing childhood mortality. Vaccine coverage refers to the percentage of people in a defined population that has received a particular dose of a vaccine, or schedule of vaccine doses. Improving coverage of vaccination is instrumental in preventing additional deaths and reaching targets that have been set for the elimination of vaccine-preventable diseases. In Tshwane District, South Africa, vaccine coverage for the population under one year is not optimal, with some areas reporting coverage levels as low as 44%, and others reporting coverage levels well over 100%. There has been no systematic exploration of the issues that have led to these estimates. Aim: To explore the factors that influence vaccine coverage in children under the age of one year, both in terms of the implementation of the vaccine programme and the process by which vaccine coverage is calculated, in Tshwane District, Gauteng, South Africa. Methods: A cross-sectional exploratory qualitative study design was used to achieve the objectives, through in-depth interviews with key-informants involved in vaccine programme implementation and coverage estimation, including nurses; managers at the facility, sub-district, district and provincial levels; and information system managers. Additionally, a focus group discussion was conducted with a ward-based outreach team. Transcripts were inductively coded and analysed, and the Consolidated Framework for Implementation Research was used to interpret the themes, in order to identify the barriers and facilitators to vaccine coverage in Tshwane. Results: Factors emerged both in terms of facilitators and barriers to vaccine coverage in Tshwane. Key facilitators were found to be: perceptions of success in the supply chain of vaccines, and high levels of engagement in achieving vaccine coverage. Key barriers were found to be: lack of mobile clinics, hindering access to services; a hierarchical, top-down approach to decision-making in removing defaulter-tracing registers; the complex process of deriving population estimates for calculating coverage rates; inefficient and ineffective data collection processes; sub-optimal data quality, and inadequate representation of the private sector. Discussion: There was a perception of high-level commitment to the success of EPI in Tshwane. The barriers to implementation of EPI are multifactorial, at all levels of the healthcare system. Coverage estimates for individual sub-districts may not be an accurate depiction of the true performance of EPI, due to inaccuracies in both the estimation of the denominator (population estimates) and the numerator (number of doses administered) of the vaccine coverage indicator. There is an opportunity for policy-makers to address highlighted issues, for example by re-instating defaulter-tracing registers and conducting an immunisation survey.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Epidemiology (Implementation Science) September, 2019